2022
DOI: 10.3390/biomedicines10092273
|View full text |Cite
|
Sign up to set email alerts
|

Serum Magnesium Levels in Patients with Obstructive Sleep Apnoea: A Systematic Review and Meta-Analysis

Abstract: Aims: Obstructive sleep apnoea (OSA) affects patients’ quality of life and health. Magnesium (Mg) is an essential mineral and a potent antioxidant. Mg deficiency can worsen oxidative stress caused by sleep deprivation or disorders. The impact of OSA on serum Mg levels and its health consequences remain unclear. Data Synthesis: This study systematically reviewed clinical studies investigating the serum Mg levels of OSA patients and the potential relationships with other biomarkers. Six articles were included fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…The correlation between Mg 2+ status and sleep quality within our research sample of APs aligns with previous observational studies conducted on the general population, as reviewed recently by Arab and coworkers [ 25 ]. Notably, sleep deprivation appears to decrease Mg 2+ levels in patients suffering from OSA [ 26 ], a condition commonly observed among APs [ 10 ]. In addition, Mg 2+ levels tend to improve after treatment, mirroring the reduction in OSA severity [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between Mg 2+ status and sleep quality within our research sample of APs aligns with previous observational studies conducted on the general population, as reviewed recently by Arab and coworkers [ 25 ]. Notably, sleep deprivation appears to decrease Mg 2+ levels in patients suffering from OSA [ 26 ], a condition commonly observed among APs [ 10 ]. In addition, Mg 2+ levels tend to improve after treatment, mirroring the reduction in OSA severity [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, sleep deprivation appears to decrease Mg 2+ levels in patients suffering from OSA [ 26 ], a condition commonly observed among APs [ 10 ]. In addition, Mg 2+ levels tend to improve after treatment, mirroring the reduction in OSA severity [ 26 ]. A randomized controlled trial involving 46 elderly individuals with insomnia found that magnesium supplementation improved sleep quality [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic OSA-related changes in ventilation and gas exchange may lead to electrolyte imbalances, promoting QTc prolongation and predisposition to the development of polymorphic ventricular tachycardia [ 42 , 77 ]. Specifically, hypokalemia and hypomagnesemia have been associated with chronic untreated OSA [ 42 , 78 ]. Significant cardiac chamber remodeling also occurs due to prolonged, untreated OSA.…”
Section: Mechanism Of Action Of Cardiovascular Effectsmentioning
confidence: 99%
“…Finally, increased oxidative stress also implicates depletion in circulating electrolytes, which are often a cofactor of several antioxidant enzymes. In particular, according to a recent meta-analysis by Al Wadee et al, OSA patients showed significantly reduced serum magnesium levels, which correlated with worsening of cardiovascular risk biomarkers (e.g., C-reactive protein, ischemia-modified albumin, carotid intima-media thickness) [97]. Therefore, it is well established that the borders of this condition overcome the UA and that OSA, similarly to airways type-2 related disorders, should be addressed as a systemic syndrome.…”
Section: Further Implications: the Link With Sleep-related Respirator...mentioning
confidence: 99%